ANALISIS KEPEMIMPINAN VLADIMIR PUTIN DALAM KEBIJAKAN PERANG RUSIA-UKRAINA 2021-2023: PENDEKATAN SMALL THEORY: HOLSTI - Ovilya Audre Fahriz Nasution (2023)
This thesis discusses policy under the Vladimir Putin's leadership within Russia-Ukraine war in 2021-2023. Vladimir Putin can be categorized as a World Leader based on Small Theory from Ole Holsti. Russia's domination of several countries makes it dominant, which is motivated by Putin's personality. Russia, under the leadership of Vladimir Putin, was faced with various successes and polemics as well. Many people think that the Russian presidential election was rigged so that Vladimir Putin could serve several terms as president of Russia. The background of Vladimir Putin is one of the determinants of Russia's policy decisions. With the courage he had, it caused the countries around Russia to become worried about Russia's strength. Likewise, Ukraine wants to join NATO to seek protection from Russian domination in Eastern Europe. This did not make Russia to mitigates its desire to be able to control Ukraine and get a conflict with Ukraine. Even though he received censures and punishments from several countries, his personality which is calmness and firmness possessed by Vladimir Putin made Russia's strength not diminish.